1998
DOI: 10.1901/jeab.1998.69-103
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Effects of Unsignaled Delayed Reinforcement on Key Pecking of Pigeons Under Variable‐interval Schedules

Abstract: Three experiments were conducted to test an interpretation of the response-rate-reducing effects of unsignaled nonresetting delays to reinforcement in pigeons. According to this interpretation, rates of key pecking decrease under these conditions because key pecks alternate with hopper-observing behavior. In Experiment 1, 4 pigeons pecked a food key that raised the hopper provided that pecks on a different variable-interval-schedule key met the requirements of a variable-interval 60-s schedule. The stimuli ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 28 publications
3
20
0
3
Order By: Relevance
“…Experiment 1 showed that reinforcers dependent upon a spatially separated but topographically and functionally identical alternative response reduced target responding in extinction more than an equal rate of response‐independent food presentations. Thus, the alternative response of keypecking producing food reinforcers interfered with target responding more than the responses occurring in the presence of response‐independent reinforcers (e.g., hopper attending; Schaal, Shahan, Kovera, & Reilly, ; Staddon & Simmelhag, ). Unfortunately, the present study did not assess the extinction of target responding on its own to compare target responding with and without the alternative stimulus and to assess the extent to which those other responses might have interfered with target responding (cf.…”
Section: Discussionmentioning
confidence: 99%
“…Experiment 1 showed that reinforcers dependent upon a spatially separated but topographically and functionally identical alternative response reduced target responding in extinction more than an equal rate of response‐independent food presentations. Thus, the alternative response of keypecking producing food reinforcers interfered with target responding more than the responses occurring in the presence of response‐independent reinforcers (e.g., hopper attending; Schaal, Shahan, Kovera, & Reilly, ; Staddon & Simmelhag, ). Unfortunately, the present study did not assess the extinction of target responding on its own to compare target responding with and without the alternative stimulus and to assess the extent to which those other responses might have interfered with target responding (cf.…”
Section: Discussionmentioning
confidence: 99%
“…To the extent that mice consumed sucrose pellets moments after the lever press that produced them, these conditions are analogous to those arranged in studies of unsignaled, non-resetting delayed reinforcement (see Lattal, 2010). Therefore, the lower estimates of response time under sucrose pellets likely resulted from the effects of intermittent delayed reinforcement of lever pressing (or releasing), and greater coupling of non-target responses (Shahan & Lattal, 2005; Schaal, Shahan, Kovera, & Reilly, 1998). …”
Section: Discussionmentioning
confidence: 99%
“…There is some empirical evidence to suggest that a temporal delay to reinforcer delivery in an operant task may increase the variability of pigeons’ terminal behavior. In a key-pecking task in pigeons, Schaal, Shahan, Kovera, and Reilly (1998, Exp. 3) observed that variability in the latency to consume grain reward was greater when there was a 3-s interval between an operant response (i.e., the key peck) and the delivery of grain than when grain was delivered immediately after the response.…”
Section: Methodsmentioning
confidence: 99%